New Research and Developments of Water-Soluble Vitamins - Eskin, N. A. M. (Neason Akivah Michael) (Advances in food and nutrition research ;, 2018)
New Research and Developments of Water-Soluble Vitamins, Volume 83, provides updated knowledge about nutrients in foods and how to avoid their deficiency, especially for those essential nutrients that should be present in the diet to reduce disease risk and optimize health. The book provides the latest advances on the identification and characterization of emerging bioactive compounds with putative health benefits. With up-to-date information on food science, including raw materials, production, processing, distribution and consumption, it is an ideal resource for nutritionists and researchers alike.